2020
DOI: 10.1155/2020/9436068
|View full text |Cite
|
Sign up to set email alerts
|

Prevalent Health Problems among Nepalese Underground Construction Workers

Abstract: Background. Workplace is associated with exposure to various products, which can be associated with adverse health outcomes. It is true with underground construction work. This study calculated the prevalence of common health problems among Nepalese underground construction workers in comparison to heavy construction workers. This type of study is rare in the context of Nepal and other developing countries, and we hope that the findings will help to take precautions for the prevention of these conditions. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
1
3
0
2
Order By: Relevance
“… 38 In addition, there are studies that investigate the influence of poor lifestyles including smoking, heavy drinking, and bad diet that are risk factors for the above diseases among construction workers, 39 40 41 while there is study suggested that occupational exposure to noise, cold environment, particulate air pollution and underground environment can increase the risk of cardiovascular diseases. 12 42 43 However, we think it is difficult to define the work-relevance of it because the non-occupational risk factors such as age and lifestyle contribute to high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 38 In addition, there are studies that investigate the influence of poor lifestyles including smoking, heavy drinking, and bad diet that are risk factors for the above diseases among construction workers, 39 40 41 while there is study suggested that occupational exposure to noise, cold environment, particulate air pollution and underground environment can increase the risk of cardiovascular diseases. 12 42 43 However, we think it is difficult to define the work-relevance of it because the non-occupational risk factors such as age and lifestyle contribute to high.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of occupational injuries in the construction workers, it has been reported to be associated with various factors such as work duration, vibration tools, hazard awareness, alcohol consumption, and working environment. 42 44 …”
Section: Discussionmentioning
confidence: 99%
“…An American study ( 9 ) clarified that compared with white-collar workers, construction workers had increased odds of arthritis (66.2%), back problems (36.3%), work disability (36.3%), chronic lung disease (15.2%), and work-related injuries (4.2%) after controlling for possible confounders. Another study in Nepalese ( 10 ) indicated that Upper respiratory tract infection (23.4%) and injuries (16.7%) are the most common presentation among construction workers.…”
Section: Introductionmentioning
confidence: 99%
“…В ходе подземных работ, связанных с ПВ, у 23,4 % рабочих диагностируются инфекции верхних дыхательных путей; артериальная гипертензия (АГ) чаще выявляется у лиц, занятых на работах в туннеле, -13,9 % (у работающих на поверхности -4,9 %; p < 0,05); и наоборот, количество случаев острого гастроэнтерита больше у работников, занятых на поверхности, -9,9 %, тогда как у лиц, трудящихся на глубине, -3,7 % (p < 0,05) [22].…”
unclassified
“…В структуре заболеваний органов пищеварения наибольший удельный вес приходится на заболевания отделов желудочно-кишечного тракта K20-К31.9 и уступающих им в 2,0 раза болезней желчевыводящей системы и поджелудочной железы K80-К87.9. Определенную роль в развитии данных патологий имеют не только поведенческие факторы риска (нарушение правил рационального питания, наличие вредных привычек, дистресс), но и ПВ, чье воздействие значимо для тканей желудка [22].…”
unclassified